Tingkat Pengetahuan Ibu Tentang Materi Kelas Ibu Hamil di Puskesmas Tegalrejo Kabupaten Magelang - Fatimah Sari; Emy Yulianti (LPPM STIKES Guna Bangsa, 2015)
Background : The maternal mortality rate in Indonesia was high and the effort required to reduce maternal mortality - an effort that is associated with pregnancy, parturition and postpartum. One solution is through the study of pregnant women. Class of pregnant woman is a means to learn together about the health of pregnant woman , in the form of face-to -face in a group that aims to improve the mother’s knowledge and skill about pregnancy and prenatal care, postpartum care, newborn care, myths, infectious diseases and a birth certificate. Objective : To be known the mother’s Knowledge Level about the material class of pregnant women, class of pregnant women definition, Pregnancy, parturition, Postpartum and postpartum family planning, newborn care and infectious diseases at the health center district Tegalrejo Magelang . Methods : This study used a descriptive study using a cross - sectional approach. The sampling method in this study was the sample saturated with the number of samples in this study were 30 respondents. The research instrument is enclosed questionnaire filled in by the respondent. The analysis used in this study using univariate analysis. Results : Pregnant woman in the region Tegalrejo health center, Magelang regency in 2013 mostly had a good knowledge amounted to 86.7 % and enough knowledge about the class material amounted to 13.3 %. Conclusion : Mother’s level of knowledge about pregnant woman class in Tegalrejo health centers Magelang regency can be categorized good knowledge of as many as 26 respondents ( 86.7 % ).